Afatinib: An overview of its clinical development in non-small-cell lung cancer and other tumors. (January 2016) - Giordano, Pasqualina; Manzo, Anna; Montanino, Agnese; Costanzo, Raffaele; Sandomenico, Claudia; Piccirillo, Maria Carmela; Daniele, Gennaro; Normanno, Nicola; Carillio, Guido; Rocco, Gaetano; Bianco, Roberto; Perrone, Francesco; et al.
Abstract: Afatinib is an oral, irreversible, tyrosine kinase inhibitor (TKI) of EGFR, HER2 and HER4. According to phase I studies, the recommended dose of afatinib was 50 mg daily. Rash, acne, diarrhea and stomatitis were the most common adverse events. Afatinib failed to demonstrate an improvement in overall survival in unselected heavily pretreated NSCLC patients (Lux-Lung-1). On the contrary, the Lux-Lung-3 and -6 trials met the primary end point, demonstrating a significant increase in terms of PFS with afatinib compared with chemotherapy in the first line treatment of EGFR mutant patients. Moreover, in both studies, afatinib improved overall survival in patients with exon 19 EGFR deletion (31.7 vs 20.7 months; HR: 0.59, p  = 0.0001). The results of ongoing randomized trials should further clarify the efficacy of afatinib compared with first-generation TKIs in advanced NSCLC, its activity in the adjuvant and neoadjuvant settings, as well as its efficacy in other tumors.